Pengaruh Indeks Pembangunan Manusia (IPM) dan Kemiskinan Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Jawa Timur Tahun 2021 - Risma Ma’rifatul Ulumi; Zainal Abidin; Alivia Salsabila; Dhima Eva Mariana (Pusat Riset dan Inovasi Nasional, 2024)
Poverty is a serious problem that is always faced by a country that must be overcome immediately. In addition to being a problem, poverty is also a benchmark for socioeconomic conditions in measuring the success of development carried out by the government in a region / region. On the other hand, the Human Development Index (HDI) is one of the important indicators to measure success in efforts to build the quality of human life, and has an important impact on economic growth. Economic growth is the spearhead considering the correlation between HDI and poverty. This research was conducted to determine the influence of the human development index variable and poverty as the independent variable on economic growth in East Java as the dependent variable. The analysis used is quantitative analysis with multiple regression analysis methods in data with 2021 data and cross section data from 37 districts/cities in East Java and the conclusion is that all the independent variables used in this research have a significant effect on the amount of economic growth in East Java. either simultaneously or partially.